Relationship between perceived teacher support and learning engagement among adolescents: Mediation role of technology acceptance and learning motivation - An, Fuhai; Yu, Jingyi; Xi, Linjin (Frontiers in Psychology, 2022)
This study is aimed at investigating the relationship between perceived teacher support and learning engagement and exploring the mediation role played by technology acceptance and learning motivation. It adopted a structural equation modeling (SEM) approach, with sampling 467 students from four middle schools in eastern China. The research findings showed that perceived teacher support is significantly associated with learning engagement. Learning motivation plays a mediating role in the relationship between perceived teacher support and learning engagement. There is the chain mediating effect of technology acceptance and learning motivation on the relationship between perceived teacher support and learning engagement. All of these are of great importance for the teachers in the middle schools, as they help to increase students’ engagement with learning activities considering the background of the deep integration of information technology and education teaching.